Analisis Metode Perancangan dan Evaluasi UI/UX: Sebuah Tinjauan Literatur Sistematis - Richi, Michael; Gunawan, Jenifer; Michael, Michael; Farisi, Ahmad (MDP Student Conference, 2025)
The swift development of technology has positioned User Interface (UI) and User Experience (UX) design as essential components for the success of digital products. This research aims to investigate the methods and tools used in designing and evaluating UI and UX through a Systematic Literature Review (SLR) conducted over the 2022–2024 period. Data were gathered via Google Scholar searches using the keyword "UI/UX Design." Results indicate that the Design Thinking approach is the most widely adopted, featured in 13 journals, while Prototyping and User-Centered Design are utilized in 4 journals each. Among design tools, Figma emerges as the most frequently used, mentioned in 20 studies, while Usability Testing is the leading evaluation method. The main areas of focus for UI/UX applications are sales, education, and service. This research underscores the significant influence of design methods and tools on UI/UX quality and user satisfaction.